PENERAPAN METODE ACTIVITY-BASED-COSTING SYSTEM DALAM PENENTUAN TARIF JASA RAWAT INAP PADA RUMAH SAKIT HUSADA UTAMA SURABAYA. - ., Hwihanus; Latuconsina, Jalib Umar (JEA17: Jurnal Ekonomi Akuntansi, 2016)
This study aims to determine how the application of the method of Activity-Based Costing in determining the tariff for inpatient hospital Husada Utama Surabaya and compared with a rate home services inpatient approved hospital with tariff services using Activity-Based Costing the approach of activity -aktivitas in providing products or services to determine the amount of the costs incurred. This research uses descriptive method. Research using primary data with a direct review of the research object, conduct interviews and make observations or direct observations. Inpatient services tariff calculation using the ABC method, performed in two stages. That is the first expense traced to the activity which raises the cost and the second stage charge activity to the product. While the rates obtained by adding the cost of hospitalization with the expected profit. The results obtained from the calculation of rates of hospitalization services using Activity-Based Costing namely to class Suite Rp. 1,434,298, Rp VVIP class. 1,141,516, VIP Rp. 757 680, Class I USD. 706 888, class II Rp. 643 385, and class III Rp. 616 269. So in the ABC method, has been able to allocate the cost of assets to each room is right by the consumption of each activity. From the results of this study using the assumption, researchers recommend that hospital is expected to reduce rates of hospitalization services in class suite, VVIP and VIP in order to attract patients to use the services of hospitalization. As for Class I, Class II and Class III, if the tariff wants to be maintained, it is recommended to class I order the tariff was increased to get a big profit, and for class II and class III is expected to add beds or full capacity.Keywords: Activity Based Costing, Hospitals, Rates services, Inpatient